KINERJA : SAHAM SYARIAH VS SAHAM KONVENSIONAL - Maulita, Dian (JURNAL RISET AKUNTANSI TIRTAYASA, 2021)
This research aims to analyze the difference in the performance of sharia stocks with conventional stocks, analyzed from independent variables namely return (return), risk, and coefficient of variation between sharia stocks and conventional stocks. This research uses a quantitative approach with independent t-test samples. The population of this study is a company listed on the Indonesia Stock Exchange in the period 2016-2018. Sharia stocks refer to companies that entered the Jakarta Islamic Index (JII) in the period 2016-2018. conventional shares refer to companies that entered IDX30 in the period 2016-2018. Sample selection using purposive sampling. There are 6 issuers of sharia shares, while conventional stocks as many as 6 issuers. data analyzed with SPSS version 25. Based on the results of inference analysis usingindependent sample t-testshows that: 1) There is no difference in annual return rate between sharia and conventional stocks, 2) There is no annual risk difference between sharia and conventional stocks, 3) There is a difference in the coefficient of variation between sharia and conventional stocks.